MALAY-BASED HERITAGE TOURISM DEVELOPMENT IN BENGKALIS REGENCY - Reski Lestari tari; Ade Idra Suhara (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
The purpose of this study was to determine the development of heritage-based tourism in Bengkalis Regency. Geographically, Bengkalis Regency is a district directly facing the Malacca Strait and directly adjacent to neighboring Malaysia. This makes Bengkalis Regency one of the entry points for foreign nationals who want to make visits or tours to Bengkalis and its surroundings. The research method in this study is a descriptive analysis method with a qualitative approach. As a result, the tourism potential in Bengkalis Regency has not been properly explored, but it is very promising and should be developed. The geographical condition of Bengkalis Regency, which consists of islands and coastal areas as well as the atmosphere of community life and local culture that is typical of Malays, is one of the tourist destinations in Riau Province, especially in Bengkalis Regency. and the factors that influence its development include the strategic geographical location of Bengkalis Regency, the support of relevant agencies in the development and management of tourist objects, and Bengkalis Regency as a historical city with various kinds of areas and cultural heritage.